Autentiskuma problemātika folkloras kustībā Latvijā - Gintere, Beāte (Latvijas Universitāte, 2012)
Bakalaura darba mērķis ir apskatīt un analizēt jēdziena “autentisks” izpratni un nozīmi folkloras kustībā Latvijā, šīs izpratnes problemātiku un sekas. Darbā gaitā tika izvirzīta un pierādīta hipotēze — autentiskumam ir liela nozīme Latvijas folklorā, taču tā traktējums folkloras kustības kontekstā ir ideoloģisks un tā pielietojums ir diezgan nekonkrēts un subjektīvs. Autentiskums ir viens no konceptuāli nozīmīgākajiem atslēgvārdiem Latvijas folkloras kustībā. Autentiskuma problemātika un tās dažādie traktējumi ir ietekmējuši folkloras kustību, un šī ietekme būtu jāpēta kompleksi, no dažādu akadēmisko disciplīnu (socioloģijas, psiholoģijas, filozofijas, mākslas zinātnes, muzikoloģijas, tūrisma industrijas u. c) viedokļa, jo autentiskuma paradigmas ietekmi un refleksiju folkloras kustībā nav iespējams pētīt tikai no folkloristikas skatpunkta.

The goal of this Bachelor's thesis is to inspect and analyse understanding and significance of the term “authentic” regarding neo-folklore movement in Latvia, as well as problems and consequences that stem from this understanding. In this work a hypothesis has been proposed and proven which suggests that authenticity has a great significance in Latvian folklore, however its definition in the context of the Latvian neo-folklore movement is ideological and its usage is fairly vague and subjective. Authenticity is one of the conceptually most significant keywords in the Latvian neo-folklore movement. Authenticity's problems and their different subjective definitions have made a huge impact upon the neo-folklore movement and this impact should be investigated as a complex topic from the point of view of different academic disciplines (such as sociology, psychology, philosophy, art science, musicology, tourism industry etc.) as the authenticity paradigm's influence and reflection on neofolklore movement can not be researched only from the single perspective of folkloristics.
The Problem of Authenticity in Latvian Neofolklore Movement
Keywords: Filoloģija